Two novel mutations in the BCKDHB gene that cause maple syrup urine disease - Bingjuan Han; Bingchao Han; Bin Guo; Yingxia Liu; Zhiyang Cao (Pediatrics and Neonatology)
Background: Maple syrup urine disease (MSUD) is a rare metabolic disorder of autosomal recessive inheritance caused by decreased activity of branched-chain α-ketoacid dehydrogenase complex (BCKD). Mutations in the three genes (BCKDHA, BCKDHB and DBT) are associated with MSUD. Here, we describe the presenting symptoms, clinical course and gene mutation analysis of a Chinese boy with MSUD. Methods: Plasma amino acid analysis was performed by tandem mass spectrometry and the levels of organic acids in urine were measured with gas chromatography-mass spectrometry. The BCKDHB gene was sequenced by Sanger method. Furthermore, the significance of the novel mutations was predicted by Polyphen and Mutationtaster. After diagnosis, the patient was fed with protein-restricted diet to reduce intake of BCAA and was treated with l-carnitine. Metabolic parameters, clinical presentation and mental development were followed up. Results: The patient was diagnosed as MSUD. Two novel BCKDHB mutations (c.523 T > C and c.478-25_552del100) were identified. In silico analysis predicted that the two mutations were “disease causing”. The boy tolerated the treatment well and had symptomatic improvement. He presented with mild hypotonia and had nearly normal DQ scores at the age of 10 months. The two novel mutations resulted in the clinical manifestations of MSUD. Our results may reflect the heterogeneity of the pathogenic variants found in patients with MSUD. Key Words: BCAA, BCKD, BCKDHB, gene mutation, maple syrup urine disease